Providing guaranteed services without per flow management. - Stoica, Ion (Computer communication review.)
Existing approaches for providing guaranteed services require routers to manage per flow states and perform per flow operations [9, 21]. Such a stateful network architecture is less scalable and robust than stateless network architectures like the original IP and the recently proposed Diffserv [3]. However, services provided with current stateless solutions, Diffserv included, have lower flexibility, utilization, and/or assurance level as compared to the services that can be provided with per flow mechanisms.In this paper, we propose techniques that do not require per flow management (either control or data planes) at core routers, but can implement guaranteed services with levels of flexibility, utilization, and assurance similar to those that can be provided with per flow mechanisms. In this way we can simultaneously achieve high quality of service, high scalability and robustness. The key technique we use is called Dynamic Packet State (DPS), which provides a lightweight and robust mechanism for routers to coordinate actions and implement distributed algorithms. We present an implementation of the proposed algorithms that has minimum incompatibility with IPv4.